Total Pectoral Muscle Area and Prognostic Nutritional Index Provide Complementary Prognostic Information for Patients Hospitalized with HFmrEF/HFrEF - Çetin Alak; Hasan Emin Kaya; Fazıl Çağrı Hunutlu; Muhammed Batuhan Daştan; Zeynep Kumral; Tunay Şentürk (Journal of Clinical Medicine, 2026)
Background: Skeletal muscle depletion and malnutrition are common in heart failure (HF) and are associated with poor outcomes. Whether imaging-derived skeletal muscle reserve and laboratory-based nutritional indices provide complementary prognostic information remains unclear. We evaluated the prognostic value of total pectoral muscle area (TPMA), Prognostic Nutritional Index (PNI), and Controlling Nutritional Status (CONUT) scores in patients hospitalized with HFmrEF/HFrEF. Methods: In this retrospective single-center study, consecutive patients hospitalized with decompensated HF between 2017 and 2025 who underwent thoracic computed tomography were included. TPMA was measured at the T4 level. Nutritional status was assessed using PNI and CONUT. Receiver operating characteristic analysis, Kaplan–Meier analysis, Spearman correlation, and Cox regression were used to evaluate long-term all-cause mortality. Results: A total of 138 patients (median age 66 years; 35.5% women) were included. During a median follow-up of 34.4 months, 87 patients (63.0%) died. Non-survivors had lower TPMA (2589 vs. 3012 mm2, p = 0.002) and PNI (46.0 ± 5.5 vs. 50.2 ± 7.2, p < 0.001). TPMA (AUC 0.661, p = 0.001) and PNI (AUC 0.663, p = 0.001), but not CONUT (AUC 0.561, p = 0.226), predicted mortality. TPMA correlated modestly with PNI (ρ = 0.325, p < 0.001). Low TPMA (